Breast carcinoma and metastasis to fibroid - Bedoya H., Mariano (2015)
It is a patient of our particular clientele white 56-year-old widow, a native of France, comes from Miraflores (Lima). Pathological personal antecedents, unimportant. Physiological personal history: menarche at age 14. 4/30 Cataremia type: regular in quantity and presentation, without pain. First sex at age 20 without changing the catameral pace. Last sexual relationship 10 years ago. Gestation: 3 autócicos deliveries. No abortions. In April 1962, see the presence of a tumor in the right breast, which at first was the size of a plum and over the course of three months has grown twice. It presents no inconvenience to other organs